Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Publisher: Cambridge University Press
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Publisher: Routledge
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi